Governor and state administration - Khanna, R.S. (1994)
"The author focuses discussion on governor's powers and situations in which their exercise causes controversies and accusations against him. Particularly with regard to imposition of President's Rule and in the changing context of new economic policy he gives illustrations from case law. The author also gives suggestions regarding selection, transfer and termination of governor to remove prevailing uncertainties"
Keywords: Public administration - India; Governors - Powers and duties - India; Governors